A combined current density technique for the electrochemical oxidation of perfluorooctanoic acid (PFOA) with boron‐doped diamond. (9th July 2020) - Ensch, Mary; Rusinek, Cory A.; Becker, Michael F.; Schuelke, Thomas
Abstract: Perfluoroalkyl substances (PFAS) have unique properties that limit their degradability in the environment. One of these PFAS is an acid (PFOA). Electrochemical oxidation is a promising method for remediation, but energy costs are high. To limit the energy consumption, this study used a boron‐doped diamond (BDD) electrode stack and a combined current density technique that employed 50 mA/cm 2 for the first 0.25 hours then lowered the current density to 1, 5, or 10 mA/cm 2 . This technique is similar to one developed previously; however, that method was only developed for compounds comprising of carbon, oxygen and nitrogen, whereas PFAS have the addition of fluorine. For the degradation of PFOA, the combined current density of 50 and 5 mA/cm 2 (50&5) allowed for a 37% reduction in energy usage to obtain 75% defluorination compared to using 50 mA/cm 2 alone. Further investigation into remediating an ion‐exchange regeneration solution shows great promise.